Meet the Crew at the Zoo : Mysteries on Zoo Lane #1 - Giff, Patricia Reilly; Carter, Abby (New York : Holiday House, 2020)
Luke is unhappy about leaving his home and abuelo when his father takes a job at a New York zoo, but soon he has new friends and a mystery to solve. Includes facts about zoo animals and wildlife.
Ages 7 and up.
Grades 2-3.
Keywords: Family life -- Fiction; Mystery and detective stories; Zoos -- Fiction; Moving, Household -- Fiction; Friendship -- Fiction; Zoo animals -- Fiction